The relationship between physical activity, body image, and self-esteem in adolescents - Kevser Sevik Kacmaz; Besime Bilmez (Anatolian Journal of Health Research, 2026)
Aim: To investigate the relationships among physical activity, body image, and self-esteem in adolescents. Methods: A cross-sectional design was employed. A total of 246 high school adolescents were enrolled. The physical activity level of the adolescents was assessed using the International Physical Activity Questionnaire-Short Form (IPAQ-SF), body image perception was assessed using the Body Image Scale (BIS), and self-esteem was evaluated using the Rosenberg Self-Esteem Scale (RSE). The associations between the test scores were determined with Pearson's correlation analysis. Results: The mean age of the adolescents was 15.55 ± 1.32 years, and the mean body mass index was 20.90 ± 3.56 kg/m2. The mean IPAQ-SF score was 2845.56 MET/week, the mean BIS score was 58.02 ± 11.09, and the mean RSE score was 20.20 ± 5.30. The IPAQ-SF was moderately and negatively correlated to the BIS (r= -0.424) and moderately correlated to the RSE (r= 0.407) (p